2014
DOI: 10.1095/biolreprod.113.116681
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Basal Cells Are Distinct from Dendritic Cells and Macrophages in the Mouse Epididymis1

Abstract: The epithelium that lines the epididymal duct establishes the optimal milieu in which spermatozoa mature, acquire motility, and are stored. This finely tuned environment also protects antigenic sperm against pathogens and autoimmunity, which are potential causes of transient or permanent infertility. The epididymal epithelium is pseudostratified and contains basal cells (BCs) that are located beneath other epithelial cells. Previous studies showed that in the mouse epididymis, BCs possess macrophage-like chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 62 publications
3
56
0
Order By: Relevance
“…Due to their proximity and morphological similarities, BCs have occasionally been confused with Mϕ (Seiler, et al, 2000, Seiler, et al, 1999, Seiler, et al, 1998, Yeung, et al, 1994). Although a role of BCs in immune regulation cannot be excluded, others and we have shown that BCs and Mϕ constitute two clearly distinct cells types (Serre and Robaire, 1999, Shum, et al, 2014). In addition to halo cells and Mϕ, dendritic cells have been identified in the murine epididymis based on the expression of markers such as CD11c, CD103 and MHC class II (Da Silva, et al, 2011).…”
Section: Are Macrophages and Dendritic Cells The Sentinels Of The Epimentioning
confidence: 69%
See 1 more Smart Citation
“…Due to their proximity and morphological similarities, BCs have occasionally been confused with Mϕ (Seiler, et al, 2000, Seiler, et al, 1999, Seiler, et al, 1998, Yeung, et al, 1994). Although a role of BCs in immune regulation cannot be excluded, others and we have shown that BCs and Mϕ constitute two clearly distinct cells types (Serre and Robaire, 1999, Shum, et al, 2014). In addition to halo cells and Mϕ, dendritic cells have been identified in the murine epididymis based on the expression of markers such as CD11c, CD103 and MHC class II (Da Silva, et al, 2011).…”
Section: Are Macrophages and Dendritic Cells The Sentinels Of The Epimentioning
confidence: 69%
“…While flow cytometry is the most convenient way to simultaneously analyze multiple cellular markers, it requires the disruption of tissues and the preparation of single-cell suspensions. This procedure can be misleading in the epididymis, particularly for the CX3CR1 + CD11c + cells that are embedded in the initial segment epithelium (Da Silva, et al, 2011, Shum, et al, 2014, Smith, et al, 2014). These highly ramified cells are found mostly in the IS, where they establish extremely intricate interactions with surrounding epithelial cells and occasionally communicate with the luminal milieu.…”
Section: The Epididymis Dcs and Mϕ In The 21st Centurymentioning
confidence: 99%
“…The seabream Aqp1aa ortholog also shows a conserved localization in the apical microvilli of the spermatic duct epithelium at the resting stage, whereas at spermiation this channel is no longer expressed by the epithelial cells and it appears only in the apical membrane of endothelial cells of blood vessels within the connective tissue, as previously reported in the rat (Badran & Hermo, 2002;Oliveira et al 2005). However, the tandemly duplicated Aqp1ab paralog is exclusively expressed in dispersed interstitial lamina cells, that could represent lymphocytes or macrophages embedded within the connective tissue (Da Silva et al 2011;Shum et al 2014), which suggests the neofunctionalization of this channel in the seabream spermatic duct as observed in spermatozoa (Boj et al 2015c). Interestingly, seabream Aqp3a is also expressed in other groups of interstitial cells not expressing Aqp1ab that are located close to the epithelium of the spermtic duct, but their identities are not yet known.…”
Section: Discussionmentioning
confidence: 68%
“…; Shum et al. ), which suggests the neofunctionalization of this channel in the seabream spermatic duct as observed in spermatozoa (Boj et al. ).…”
Section: Discussionmentioning
confidence: 94%
“…This compartmentalized gene expression results in segment-specific protein secretions into the luminal fluid, creating sperm microenvironments where specific modifications in spermatozoa happen. The composition of the intra luminal milieu is defined by the pseudostratified epithelium composed of six cell types possessing distinct physiological functions: narrow and apical cells found in the proximal region of the epididymis and principal cells, clear cells, machophages, dentritic cells, basal cells and halo cells found throughout the organ (Breton et al, 2016;Da Silva and Barton, 2016;Kempinas and Klinefelter, 2014;Shum et al, 2014). Each cell type contributes to the establishment and regulation of a unique luminal environment for the concentration, maturation, storage, and viability of spermatozoa.…”
Section: A Brief Introduction To Epididymal Physiologymentioning
confidence: 99%